2000
DOI: 10.1111/j.1348-0421.2000.tb02541.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Anti‐Tumor Responses against TL Positive Lymphoma Induced by Skin Grafting and Dendritic Cell Immunization

Abstract: When the skin of Tg.Con.3-1 transgenic mice expressing the TL (thymus leukemia) antigen in most tissues is grafted on syngeneic C3H mice, it is rejected, and a cytotoxic T cell (CTL) response against the TL antigen is induced. In this study, we first demonstrated that growth of TL positive lymphoma is suppressed in mice immunized by skin grafting. Immunization with bone marrow derived dendritic cells (DCs) from Tg.Con.3-1, was also found to be associated with an anti-tumor response, but less potent than skin g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2001
2001
2004
2004

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 45 publications
(16 reference statements)
0
12
0
Order By: Relevance
“…The present study demonstrated that the staining intensity of CTL clones roughly correlated with the cytotoxic activity against TL ϩ target cells, and that TL-restricted CTL could be enriched by selecting the tetramer-positive population. These results altogether showed that the T3 b -TL tetramer prepared in this study is useful for monitoring the dynamics and magnitude of T cell responses against TL, similarly to other monitoring methods, such as cytoplasmic IFN-␥ staining and CTL assays, as we reported previously (36), although blocking tests with anti-CD3 mAb should be performed to confirm the specificity of the tetramer binding. Studies are now in progress to compare these monitoring methods to determine which one is reliable to predict in vivo antitumor responses against TL-positive tumors.…”
Section: Discussionmentioning
confidence: 87%
“…The present study demonstrated that the staining intensity of CTL clones roughly correlated with the cytotoxic activity against TL ϩ target cells, and that TL-restricted CTL could be enriched by selecting the tetramer-positive population. These results altogether showed that the T3 b -TL tetramer prepared in this study is useful for monitoring the dynamics and magnitude of T cell responses against TL, similarly to other monitoring methods, such as cytoplasmic IFN-␥ staining and CTL assays, as we reported previously (36), although blocking tests with anti-CD3 mAb should be performed to confirm the specificity of the tetramer binding. Studies are now in progress to compare these monitoring methods to determine which one is reliable to predict in vivo antitumor responses against TL-positive tumors.…”
Section: Discussionmentioning
confidence: 87%
“…When 1×10 4 TL + lymphomas were injected, most mice immunized either way survived. 20) However, when the number of TL + lymphomas was increased three-fold, i.e., 3×10 4 , all mice immunized with DCs died, although half of the skin-grafted mice survived, 20) indicating that DC immunization is the less effective of the two approaches.…”
Section: Tl As a Tumor Specific Antigenmentioning
confidence: 99%
“…35) We first tested the anti-tumor efficacy by active immunization with DCs as compared with skin grafting in a prophylactic vaccine model. 20) TL + DCs were generated in vitro from bone marrow of Tg.Con.3-1 mice with GM-CSF and injected subcutaneously (s.c.) into the backs of C3H mice three times at 2-week intervals. Two weeks after the final immunization, TL + or TL -lymphomas were injected.…”
Section: Tl As a Tumor Specific Antigenmentioning
confidence: 99%
See 1 more Smart Citation
“…Although TL − strains (e.g., C57BL/6 (B6) and C3H/He (C3H)) do not express TL in the thymus, a proportion of T lymphomas originating in these mice express TL as a serologically defined tumor antigen. 1,[10][11][12] In a previous study, we demonstrated that a certain fraction of N-butyl-N-nitrosourea (NBU)-induced lymphomas in C3H and B6 mice express TL, but the expression profiles are somewhat different between these two strains.12) TL is expressed by only a half of the C3H-derived lymphomas (8/16), but most B6-derived lymphomas are TL-positive (16/17). In another study, we derived Tg.Con.3-1 and Tg.Con.3-2 transgenic mice (C3H background) expressing T3 b -TL ubiquitously 13,14) and demonstrated that TL can serve as a transplantation antigen by grafting the skin of these mice onto syngeneic C3H.…”
mentioning
confidence: 99%